Solid-state lithium ion battery

By co-sintering the positive electrode and the solid electrolyte separately and recombining it with the metal lithium negative electrode, combining the polymer layer and the composite liquid collector, the problems of interface impedance and application range of multi-layer ceramic batteries are solved, the energy density and manufacturing ease is improved, and the energy density and manufacturing ease is achieved Matching with the metal lithium negative electrode.

CN119315089AActive Publication Date: 2025-01-14CHINA UNIV OF MINING & TECH (BEIJING)
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411439460.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-14
Estimated Expiration
2044-10-15

AI Technical Summary

Technical Problem

In the sintering process, the existing multi-layer ceramic batteries have high hardness of the positive electrode and solid electrolyte materials, resulting in large interface impedance, which limits the industrial application of solid lithium-ion batteries and cannot match the metal lithium negative electrode, limiting the application of multi-layer ceramic technology. scope.

Method used

By co-sintering the positive electrode and the solid electrolyte separately to form a multi-layer ceramic structure, then recombined with the metal lithium negative electrode, and a polymer layer and a composite fluid are arranged between the battery cells to stack the battery cells through isostatic pressure process to achieve better interface contact and bonding force.

Benefits of technology

The energy density of multi-layer ceramic batteries is improved, the application scope is broadened, the compatibility problem of the positive electrode and solid electrolyte co-fired conditions for the negative electrode materials is avoided, the manufacturing difficulty is reduced, and the cracking problem during the cycle is solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119315089A_ABST
    Figure CN119315089A_ABST
Patent Text Reader

Abstract

According to the solid-state lithium ion secondary battery and the preparation method thereof provided by the invention, the positive electrode and the solid-state electrolyte layer are co-fired to form a multi-layer ceramic structure, then the multi-layer ceramic structure is compounded with the metal lithium negative electrode and the polymer solid-state electrolyte membrane to form the battery units, and then the plurality of battery units are assembled into the battery cell with the inside connected in series through an isostatic pressing process. By utilizing the preparation method, the application range of the multilayer ceramic technology in the solid-state lithium ion battery is expanded, and the preparation method has a good industrialization prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a solid-state lithium-ion battery, and in particular to an all-solid-state lithium-ion battery. Background Art

[0002] Multilayer ceramic batteries (MLCB) are often referred to as the battery version of multilayer ceramic capacitors (MLCC), and multilayer ceramic batteries usually have a structure formed by alternating thin-film electrodes and solid electrolytes. In the prior art, multilayer ceramic batteries usually co-sinter the positive electrode, solid electrolyte layer and negative electrode, but the sintering process between the negative electrode material and the positive electrode material is quite different. For example, graphite usually requires a reducing atmosphere, and the positive electrode requires an oxidizing atmosphere. Therefore, the co-firing process of multilayer ceramics greatly limits the selection range of positive and negative electrode materials. At the same time, the performance of existing multilayer ceramics formed by hot pressing and other methods needs to be improved, and cannot fully meet the performance requirements of solid-state batteries. Summary of the invention

[0003] In order to solve the above problems, the present invention provides a high-voltage multilayer ceramic battery that can match a metal lithium negative electrode, having at least two or more battery cells including a positive electrode, a negative electrode and a solid electrolyte layer; the positive electrode and the solid electrolyte layer form a multilayer ceramic structure, and the multilayer ceramic structure is an integrated structure;

[0004] A polymer layer is arranged between the solid electrolyte layer and the negative electrode; the negative electrode contains metallic lithium; and two adjacent battery cells are electrically connected in series.

[0005] Preferably, the porosity of the multilayer ceramic structure is less than 10%; further preferably, the porosity of the multilayer ceramic structure is less than 5%.

[0006] Preferably, the positive electrode comprises a positive electrode active material layer and a positive electrode current collector, the positive electrode current collector is arranged on a side of the positive electrode active material layer away from the solid electrolyte layer, and in the solid-state lithium-ion secondary battery, at least one positive electrode current collector is electrically connected to the adjacent negative electrode.

[0007] Preferably, the negative electrode comprises a negative electrode current collector, and the negative electrode current collector is arranged between the positive electrode active material layer of the adjacent battery unit and the negative electrode or is arranged at the outermost side of the solid-state lithium-ion secondary battery.

[0008] Preferably, a composite current collector layer is further arranged between the positive electrode and the negative electrode, the composite current collector comprises a protective layer and a positive current collector and a negative current collector arranged on both sides of the protective layer, and the positive current collector and the negative current collector are electrically connected.

[0009] Preferably, the polymer layer comprises a polymer solid electrolyte and a lithium salt;

[0010] Preferably, the solid electrolyte layer includes an oxide solid electrolyte.

[0011] Preferably, the metal lithium negative electrode includes one or more of lithium foil, lithium sheet, and lithium-indium alloy.

[0012] The second invention of the present invention also provides a method for preparing the solid-state lithium-ion secondary battery as described above, comprising the following steps:

[0013] S1. Preparing a multilayer ceramic structure comprising a positive electrode active material layer and a solid electrolyte layer;

[0014] S2. The multilayer ceramic structure, polymer layer and lithium metal negative electrode prepared in the composite step SI are formed into a battery cell; and / or, the prefabricated sheet composed of the polymer layer and the lithium metal negative electrode and the multilayer ceramic structure prepared in the step S1 are formed into a battery cell;

[0015] S3. Stacking two or more battery cells prepared in step S2 to obtain a solid-state lithium-ion secondary battery, wherein the positive electrodes and negative electrodes of two adjacent battery cells are connected.

[0016] Preferably, in step S1, the positive electrode active material layer and the solid electrolyte layer are compounded to form a composite structure; and the composite structure is co-sintered under an inert atmosphere to obtain a multilayer ceramic structure.

[0017] The co-firing temperature is 600-1400°C; preferably, 800-1100°C.

[0018] Preferably, the step S1 further comprises arranging a positive electrode current collector on a side of the obtained multilayer ceramic structure away from the solid electrolyte layer.

[0019] Preferably, in step S2, a negative electrode current collector and a protective layer are provided on the side of the metal lithium negative electrode away from the polymer layer, and the negative electrode current collector is provided between the protective layer and the metal lithium negative electrode;

[0020] Preferably, in step S3, the protective layer is located between the positive electrode and the negative electrode of two adjacent battery cells.

[0021] Preferably, in step S3, the solid-state lithium-ion secondary battery is prepared by an isostatic pressing process.

[0022] Further preferably, in step S3, the stacked battery cells are processed by an isostatic pressing process to obtain a solid-state lithium-ion secondary battery.

[0023] The isostatic pressing process temperature is 80-140° C. and the pressure is 80-140 MPa.

[0024] Preferably, conductive glue is provided on the surface of the protective layer.

[0025] The present application has no special requirements on the type of conductive adhesive, and any known type of conductive adhesive can be used in the present application without violating the inventive concept of the present application, such as epoxy resin, acrylate resin, polyurethane and other conductive adhesives.

[0026] Preferably, in step S3, the solid-state lithium-ion secondary battery is prepared by an isostatic pressing process.

[0027] Further preferably, in step S3, the stacked battery cells are processed by an isostatic pressing process to obtain a solid-state lithium-ion secondary battery.

[0028] The isostatic pressing process temperature is 80-140° C. and the pressure is 80-140 MPa.

[0029] The present invention has the following technical effects:

[0030] 1. The present invention co-fires the positive electrode and the solid electrolyte layer separately, and then composites them with the negative electrode metal lithium negative electrode. This preparation process enables the multi-layer ceramic battery involved to match the metal lithium negative electrode, avoiding the problem that the co-firing conditions of the positive electrode and the solid electrolyte must be compatible with the negative electrode material, making the battery have a higher energy density and improving the application range of the multi-layer ceramic battery.

[0031] 2. The present invention provides a polymer layer between the metal lithium negative electrode and the solid electrolyte. On the one hand, the polymer layer is used to achieve good interface contact between the metal lithium and the solid electrolyte layer. At the same time, the polymer layer can avoid the reaction between part of the solid electrolyte and the metal lithium, thereby protecting the metal lithium. On the other hand, the good film-forming performance of the polymer layer plays a supporting role for the metal lithium negative electrode, thereby reducing the manufacturing difficulty of the entire battery.

[0032] 3. The present application solves the problem of hard oxide solid electrolyte particles and the interface problem between the positive electrode and the solid electrolyte layer when they are co-fired through a co-firing process.

[0033] 4. In the present application, when the solid-state lithium-ion secondary battery cell is stacked in series by an isostatic pressing process, a bonding force is given between the composite current collector and the electrode. During the cell preparation stage, a good bonding force is achieved between the multilayer ceramic structure and the current collector, and between the battery cells, so that the internally connected cells can be used normally and the cracking problem during the cycle process is avoided. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 A diagram of the structure of a battery manufactured according to an embodiment of the present invention;

[0035] 1-positive electrode current collector 2-positive electrode 3-solid electrolyte layer 4-polymer layer 5-negative electrode 6-negative electrode current collector 7-protective layer. DETAILED DESCRIPTION

[0036] References to embodiments of the present application will now be provided in detail, one or more examples of which are described below. Each example is provided as an explanation rather than a limitation of the present application. In fact, it will be apparent to those skilled in the art that various modifications and variations may be made to the present application without departing from the scope or spirit of the present application. For example, a feature described or described as part of one embodiment may be used in another embodiment to produce a further embodiment.

[0037] Therefore, it is intended that the present application covers such modifications and variations that fall within the scope of the appended claims and their equivalents. Other objects, features and aspects of the present application are disclosed in or are apparent from the following detailed description. It will be appreciated by those of ordinary skill in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the present application.

[0038] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0039] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0040] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0041] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0042] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, it is mentioned that the method may also include step (c), which means that step (c) can be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0043] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0044] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0045] The first aspect of the present application provides a multilayer ceramic battery that can match a metal lithium negative electrode, having at least two or more battery cells including a positive electrode, a negative electrode and a solid electrolyte layer; the positive electrode and the solid electrolyte layer form the multilayer ceramic structure, and the multilayer ceramic structure is an integrated structure;

[0046] A polymer layer is arranged between the solid electrolyte layer and the negative electrode; the negative electrode contains metallic lithium; and two adjacent battery cells are electrically connected in series.

[0047] Preferably, the porosity of the multilayer ceramic structure is less than 10%; further preferably, the porosity of the multilayer ceramic structure is less than 5%.

[0048] In this application, multilayer ceramics are directly sintered by positive electrode and solid electrolyte. In existing solid-state lithium-ion batteries, due to the high hardness of positive electrode and solid electrolyte materials, the interface impedance between positive electrode and solid electrolyte is a major obstacle to the industrial application of solid-state lithium-ion batteries. The positive electrode material powder is mixed with the solid electrolyte and then hot-pressed and sintered to form a highly dense composite electrode. Compared with the traditional coating and roller-pressing composite process, hot-pressing and sintering form a stronger physical and chemical bond between the positive electrode material and the solid electrolyte, effectively reducing the interface impedance and improving the dynamics. Although the existing co-sintering of solid electrolyte with positive and negative electrode materials can solve the interface problem between the positive electrode and the solid electrolyte, the sintering process cannot match the metal lithium negative electrode, which limits the application of multilayer ceramic technology in solid-state batteries.

[0049] In this application, the solid electrolyte and the positive electrode material are first co-sintered to form a positive electrode-solid electrolyte multilayer ceramic structure, which is then composited with a metallic lithium negative electrode. While the multilayer ceramic structure solves the interface problem, it also achieves the matching problem between the multilayer ceramic lithium-ion solid-state battery and the metallic lithium negative electrode.

[0050] Preferably, the positive electrode comprises a positive electrode active material layer and a positive electrode current collector, the positive electrode current collector is arranged on a side of the positive electrode active material layer away from the solid electrolyte layer, and in the solid-state lithium-ion secondary battery, at least one positive electrode current collector is electrically connected to the adjacent negative electrode.

[0051] The present application utilizes lithium-ion solid-state batteries to realize a series structure inside the battery cell, thereby increasing the voltage inside the battery cell.

[0052] Preferably, the negative electrode comprises a negative electrode current collector, and the negative electrode current collector is arranged between the positive electrode active material layer of the adjacent battery unit and the negative electrode or is arranged at the outermost side of the solid-state lithium-ion secondary battery.

[0053] Preferably, a composite current collector layer is further arranged between the positive electrode and the negative electrode, the composite current collector comprises a protective layer and a positive current collector and a negative current collector arranged on both sides of the protective layer, and the positive current collector and the negative current collector are electrically connected.

[0054] It can be understood that the positive electrode and the negative electrode are the positive electrode and the negative electrode of adjacent battery cells.

[0055] That is, a composite current collector layer is arranged between the positive electrode and the negative electrode of adjacent battery cells.

[0056] The positive / negative current collector acts as a carrier of the positive / negative active material in lithium-ion batteries, and also plays the role of forming an electron path and conducting current. The composite current collector is a new technology developed in recent years. The composite current collector can adopt a "metal-polymer material-metal" sandwich structure, with materials such as polymer insulating resin as the "sandwich" layer, and metals deposited on the upper and lower surfaces as the positive / negative current collector. Composite current collectors have obvious advantages over traditional metal foil current collectors. For example, traditional current collectors cannot be infinitely thinned because a certain mechanical strength must be guaranteed. If the current collector is too thin, it is easy to deform and break during the battery cycle. The composite current collector uses part of the organic matter to replace the metal foil material, further reducing the amount of metal used, and can prepare lighter products while ensuring safety.

[0057] In the composite current collector, the protective layer can be a polymer layer. The present application has no special requirements for the material of the protective layer. It is only used as an illustrative example, not a limitation on the scope of protection. The material of the polymer layer includes one or more of polyethylene terephthalate, polypropylene, polyethylene, polystyrene, polyvinyl chloride, polyamide, polyimide, polyvinylidene fluoride, polytetrafluoroethylene, polyphenylene sulfide and polyphenylene ether.

[0058] Since the protective layer is a polymer layer, when a short circuit occurs in the lithium-ion battery, the protective layer can block the contact between the burrs generated by the current collector, thereby preventing the lithium-ion battery from failing.

[0059] The present application has no special requirements for the thickness of the protective layer. In the case of meeting the use requirements, conventional adjustments to the thickness should be considered within the scope of protection of the present application. It is only used as an illustrative example, not a limitation on the scope of protection. The thickness of the protective layer can be 3μm to 12μm. The use of a protective layer of the above thickness is not only conducive to the preparation of the protective layer, but also can play a bearing role, and avoids excessive thickness and affecting the volume energy density of the lithium-ion battery. Specifically, the thickness of the protective layer can be but is not limited to 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm or 12μm, etc. In one embodiment, the thickness of the protective layer can be 4μm to 10μm. In another embodiment, the thickness of the protective layer can be 5μm to 11μm. In another embodiment, the thickness of the protective layer can be 6μm to 9μm.

[0060] Preferably, the protective layer has a conductive material therein.

[0061] By adding a conductive material to the protective layer, electrical connection between the positive electrode collector and the negative electrode collector is achieved. The present application has no special requirements on the type and amount of the conductive material. Known materials with electronic properties and that can be used in composite current collectors can be used in the present application. This is only used as an illustrative example, not a limitation on the scope of protection. The conductive material can be at least one of carbon nanotubes, graphene, conductive graphite, carbon black, carbon fiber, graphite, conductive ceramic powder, and composite conductive materials; it can also be at least one of aluminum, copper, nickel, copper, cobalt, tungsten, tin, lead, iron, silver, gold, platinum, or their alloys.

[0062] The added amount of the conductive material may be 0.1-50 wt % of the total protective layer.

[0063] The present application has no special requirements on the structure and material of the positive electrode current collector and the negative electrode current collector. Without violating the inventive concept of the present application, any known positive electrode current collector and negative electrode current collector can be used in the present application. It is only used as an illustrative example rather than a limitation on the scope of protection. The positive electrode current collector and the negative electrode current collector can be selected from one or more of copper, aluminum, nickel, and stainless steel. Preferably, the positive electrode current collector is aluminum and the negative electrode current collector is copper.

[0064] It is understandable that the positive electrode current collector and the negative electrode current collector can be formed by any one of physical vapor deposition, chemical vapor deposition, water electroplating, chemical plating, etc. Specifically, physical vapor deposition may include but is not limited to vacuum evaporation, magnetron sputtering, ion plating, etc., and chemical vapor deposition may include but is not limited to plasma enhanced chemical vapor deposition, thermal chemical vapor deposition, high temperature chemical vapor deposition, medium temperature chemical vapor deposition, etc. The above method makes it easier to control the thickness of the positive electrode current collector or the negative electrode current collector and reduce the difficulty of preparation. As a preferred embodiment, the positive electrode current collector or the negative electrode current collector can be formed on the surface of the protective layer by water electroplating or chemical plating. The temperature of water electroplating or chemical plating is low, which can ensure the performance stability of the protective layer during the preparation process.

[0065] Preferably, the positive electrode current collector is on the surface of the positive electrode.

[0066] Preferably, the negative electrode current collector is deposited on the surface of the negative electrode.

[0067] Preferably, a conductive structure is provided in the protective layer, and the conductive structure penetrates the protective layer, so that the positive electrode current collector and the negative electrode current collector are electrically connected.

[0068] The present application has no special requirements for the specific shape of the conductive structure. Without violating the inventive concept of the present application, any known conductive structure can be used in the present application. It is only used as an illustrative example rather than a limitation on the scope of protection. The conductive structure can be at least one of a conductive column, a conductive wire, a conductive mesh, a conductive sheet, and a conductive rod.

[0069] As an embodiment, the polymer layer includes a polymer solid electrolyte and a lithium salt;

[0070] Preferably, the polymer is selected from polyethylene glycol, polyethylene oxide (PEO), poly(p-phenylene oxide) (PPO), poly(methyl methacrylate) (PMMA), polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), polyvinylidene fluoride co-hexafluoropropylene (PVDF-HFP), polyvinyl chloride (PVC), and combinations thereof. In one variation, one or more polymer materials may have a molecular weight equal to about 10 -4 S / cm ionic conductivity.

[0071] Preferably, the lithium salt is selected from lithium hexafluorophosphate (LiPF6); lithium perchlorate (LiClO4), lithium tetrachloroaluminate (LiAlCl4), lithium iodide (LiI), lithium bromide (LiBr), lithium thiocyanate (LiSCN), lithium tetrafluoroborate (LiBF4), lithium difluorooxalatoborate (LiBF2(C2O4))(LiODFB), lithium tetraphenylborate (LiB(C6H5)4), lithium bis(oxalate)borate (LiB(C2O4)2)(LiBOB), lithium tetrafluorooxalatophosphate (LiPF4(C2O4))(LiFOP), lithium nitrate (LiNO3), lithium hexafluoroarsenate (LiAsF6), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethanesulfonyl imide) (LITFSI)(LiN(CF3SO2)2), lithium bis(fluorosulfonyl imide) (LiN(FSO2)2)(LIFSI) and combinations thereof. In certain variations, the lithium salt is selected from lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethanesulfonyl imide) (LiTFSI)(LiN(CF3SO2)2), lithium bis(fluorosulfonyl imide) (LiN(FSO2)2)(LiFSI), lithium fluoroalkyl phosphonate (LiFAP), lithium phosphate (Li3PO4), and combinations thereof.

[0072] Preferably, the solid electrolyte layer comprises an oxide solid electrolyte;

[0073] As an embodiment, the oxide solid electrolyte comprises one or more garnet ceramics, LISICON type oxides, NASICON type oxides and perovskite type ceramics. For example, the one or more garnet ceramics may be selected from the group consisting of: Li 6.5 LqCy1.75 Te 0.25 O 12 、 Li7La3Zr2O 12 、 Li 6.2 Ga 0.3 La 2.95 Rb 0.05 Zr2O 12 、 Li 6.85 La 2.9 Ca 0.1 Zr 1.75 Nb 0.25 O 12 、 Li 6.25 Al 0.25 La3Zr2O 12 、 Li 6.75 La3Zr 1.75 Nb 0.25 O 12 、 Li 6.75 La3Zr 1.75 Nb 0.25 O 12 and combinations thereof. One or more LISICON-type oxides may be selected from the group consisting of: Li 14 Zn(GeO4)4, Li 3+x (P 1-x Si x )O4 (where 0 < x < 1), Li 3+x Ge x V 1-x O4 (where 0 < x < 1) and combinations thereof. One or more NASICON-type oxides may be defined by LiMM′(PO4)3, where M and M′ are independently selected from Al, Ge, Ti, Sn, Hf, Zr, and La. For example, in certain variations, one or more NASICON-type oxides may be selected from the group consisting of: Li 1+x AlxGe 2-x (PO4)3 (LAGP) (where 0 ≤ x ≤ 2), Li 1+x Al x Ti 2-x (PO4)3 (LATP) (where 0 ≤ x ≤ 2), Li 1+x Y x Zr 2-x (PO4)3 (LYZP) (where 0 ≤ x ≤ 2), Li 1.3 Al 0.3 Ti 1.7(PO4)3, LiTi2(PO4)3, LiGeTi(PO4)3, LiGe2(PO4)3, LiHf2(PO4)3, and combinations thereof. One or more perovskite-type ceramics may be selected from the group consisting of: Li 3.3 La 0.53 TiO3, LiSr 1.65 Zr 1.3 Ta 1.7 O9, Li 2x-y Sr 1-x Ta y Zr 1-y O3 (where x = 0.75y and 0.60 < y < 0.75), Li 3 / 8 Sr 7 / 16 Nb 3 / 4 Zr 1 / 4 O3, Li 3x La (2 / 3-x) TiO3 (where 0 < x < 0.25), and combinations thereof. In one variant, one or more oxide-based materials may have an ionic conductivity greater than or equal to about 10 -5 S / cm to less than or equal to about 10 -1 S / cm.

[0074] Preferably, the oxide solid electrolyte can react with metallic lithium in an electrochemical environment.

[0075] It is understood that the oxide solid electrolyte layer of the present application can be a multi-layer structure, such as a first oxide solid electrolyte layer and a second oxide solid electrolyte layer.

[0076] The positive electrode is formed by a plurality of positive electrode active particles containing one or more transition metal cations, such as manganese (Mn), nickel (Ni), cobalt (Co), chromium (Cr), iron (Fe), vanadium (V), and combinations thereof. In some embodiments, the positive electrode electroactive material layer further includes an electrolyte, such as a plurality of electrolyte particles. The positive electrode active material layer has a thickness greater than or equal to about 1 μm to less than or equal to about 1,000 μm.

[0077] It is understood that the present application has no special requirements for the positive electrode active material. Based on the inventive concept of the present application, any known positive electrode active material can be used in the present application. Merely as a schematic example, rather than a limitation of the protection scope, the positive electrode active material is one of a layered oxide positive electrode, a spinel cathode, and a polyanion positive electrode. For example, the layered oxide (e.g., rock salt layered oxide) contains one or more lithium-based positive electrode electroactive materials selected from the following: LiCoO2 (LCO), LiNi x Mn y Co1-x-y O2 (where 0≤x≤1 and 0≤y≤1), LiNi 1-x-y Co x Al y O2 (where 0≤x≤1 and 0≤y≤1), LiNi x Mn 1-x O2 (where 0≤x≤1), and Li 1+x MO2 (wherein M is one of Mn, Ni, Co and Al and 0≤x≤1). The spinel positive electrode comprises one or more lithium-based positive electrode electroactive materials selected from the group consisting of LiMn2O4 (LMO) and LiNi x Mn 1.5 O4. The olivine-type material comprises one or more lithium-based positive electrode electroactive materials LiMPO4 (wherein M is at least one of Fe, Ni, Co and Mn). The polyanion cation comprises, for example, phosphates such as LiV2(PO4)3 and / or silicates such as LiFeSiO4.

[0078] It is understood that the positive electrode active material can be selected from a mixture of the above-mentioned materials.

[0079] Preferably, the metal lithium negative electrode includes one or more of lithium foil, lithium sheet, and lithium-indium alloy.

[0080] The second invention of the present invention also provides a method for preparing a solid-state lithium-ion secondary battery, comprising the following steps:

[0081] S1. Preparing a multilayer ceramic structure comprising a positive electrode active material layer and a solid electrolyte layer;

[0082] S2. The multilayer ceramic structure, polymer layer and lithium metal negative electrode prepared in the composite step SI are formed into a battery cell; and / or, the prefabricated sheet composed of the polymer layer and the lithium metal negative electrode and the multilayer ceramic structure prepared in the step S1 are formed into a battery cell;

[0083] S3. Stacking two or more battery cells prepared in step S2 to obtain a solid-state lithium-ion secondary battery, wherein the positive electrodes and negative electrodes of two adjacent battery cells are electrically connected.

[0084] Preferably, in step S1, the positive electrode active material layer and the solid electrolyte layer are compounded to form a composite structure; and the composite structure is co-sintered under an inert atmosphere to obtain a multilayer ceramic structure.

[0085] Co-firing essentially refers to the process of mixing two or more materials and sintering them together at a certain temperature. The co-firing process of solid electrolyte and positive electrode active material is conducive to forming a dense interface and improving battery performance.

[0086] The present application has no particular restrictions on the co-sintering process. Without violating the inventive concept of the present application, all known co-sintering methods can be used in the present application. They are only used as illustrative examples rather than limitations on the scope of protection. The co-sintering process may include one of microwave induced carbon thermal shock fast sintering, pressureless sintering, hot pressing sintering, and spark plasma sintering (SPS).

[0087] Preferably, in the present application, the co-firing temperature is 600-1400°C; preferably, 800-1100°C.

[0088] As an implementation mode, sintering can be multi-stage sintering, for example, heating to 600°C at a certain heating rate, keeping warm for 3 hours, and then heating to 800°C at a certain heating rate, keeping warm for 4 hours; the present application has no special requirements for the sintering process. On the basis of not violating the inventive concept of the present application, routine adjustments to the sintering process should still be regarded as within the scope of protection of the present application.

[0089] Preferably, the positive electrode active material layer comprises a positive electrode active material and a second solid electrolyte;

[0090] Preferably, in the positive electrode active material layer, the second solid electrolyte accounts for 5-50 wt % of the positive electrode active material layer.

[0091] Since the solid-state lithium-ion battery does not contain an electrolyte, the lithium ion transport capability of the positive electrode active material layer formed by the positive electrode and the second solid electrolyte is mainly provided by the second solid electrolyte.

[0092] Preferably, the second solid electrolyte is also an oxide solid electrolyte, which may be the same as or different from the solid electrolyte in the solid electrolyte layer.

[0093] It can be understood that during the co-firing process, the solid electrolyte and the positive electrode active material layer are rapidly densified to form a ceramic structure with a porosity of <10% or even less than 5%.

[0094] It can be understood that the porosity of a composite material is the percentage of the void volume in the material to the entire composite material volume, and the porosity represents the density of the ceramic structure.

[0095] Preferably, the method of compounding the positive electrode active material layer with the solid electrolyte layer is one of coating, spraying or laminating the positive electrode active material layer and the solid electrolyte layer.

[0096] Preferably, after the solid electrolyte layer and the positive electrode active material layer are composited to obtain a green body, the green body is placed in an isostatic pressing device for cold isostatic pressing treatment.

[0097] As an embodiment, the isostatic pressing process is cold isostatic pressing.

[0098] Preferably, the step S1 further comprises arranging a positive electrode current collector on a side of the obtained multilayer ceramic structure away from the solid electrolyte layer.

[0099] It can be understood that the present application does not specifically limit the method of setting the current collector. Without violating the inventive concept of the present application, the positive electrode current collector can be directly compounded with the multilayer ceramic structure, or a metal film can be plated on the surface of the multilayer ceramic structure by methods such as magnetron sputtering.

[0100] Preferably, in step S2, a negative electrode current collector and a protective layer are provided on the side of the metal lithium negative electrode away from the polymer layer, and the negative electrode current collector is provided between the protective layer and the metal lithium negative electrode;

[0101] Preferably, in step S3, the protective layer is located between the positive electrode and the negative electrode of two adjacent battery cells.

[0102] It can be understood that the protective layer and the positive electrode current collector and the negative electrode current collector form a composite current collector structure. The composite current collector can not only reduce the thickness of the foil material, but also has higher safety performance.

[0103] Preferably, in step S3, the protective layer is located between the positive electrode and the negative electrode of two adjacent battery cells.

[0104] Preferably, in step S3, the solid-state lithium-ion secondary battery is prepared by an isostatic pressing process.

[0105] Further preferably, in step S3, the stacked battery cells are processed by an isostatic pressing process to obtain a solid-state lithium-ion secondary battery.

[0106] The isostatic pressing process temperature is 80-140° C. and the pressure is 80-140 MPa.

[0107] Preferably, conductive glue is provided on the surface of the protective layer.

[0108] The present application has no special requirements on the type of conductive adhesive, and any known type of conductive adhesive can be used in the present application without violating the inventive concept of the present application, such as epoxy resin, acrylate resin, polyurethane and other conductive adhesives.

[0109] Isostatic pressing is a method of applying equal pressure in all directions to an object through a pressurization system, so as to reduce the distance between molecules without changing the appearance and shape, thereby improving the physical properties of the substance. This method is usually carried out in a closed container, which is filled with a liquid medium. The liquid medium is pressed into the container by a high-pressure pump to apply pressure to the object in the container.

[0110] The present application improves the bonding force between the various structures in the battery cell during the pressing process of the battery cell through the hot isostatic pressing process.

[0111] The present application will be further described below with reference to specific embodiments and comparative examples.

[0112] Example 1

[0113] Preparation of multilayer ceramic structures:

[0114] Raw material preparation and mixing: lithium cobalt oxide powder with an average particle size of 10 μm and LLZO powder with a particle size of 500 nm were added into a ball mill at a mass ratio of 97:3; an appropriate amount of isopropyl ketone was added as a grinding aid, and the powder was ball milled at a speed of 500 rpm for 24 hours to ensure that the powder was evenly dispersed; after ball milling, the powder was placed in an oven at 80°C for 6 hours for drying.

[0115] Powder molding: The dried powder is ground and sieved to remove lumps; the uniform powder is loaded into a mold and hydraulically molded at a pressure of 20 MPa to obtain a green body of the positive electrode active material layer.

[0116] Electrolyte spraying and cold isostatic pressing: A 10μm thick layer of LLZO electrolyte powder is sprayed on the surface of the green body of the positive electrode active material layer, wherein the particle size of the LLZO electrolyte powder is 500nm; the sprayed green body is placed in a cold isostatic pressing device and cold isostatically pressed at a pressure of 200MPa to increase the density of the green body. The processing time is about 10 minutes, and the relative density of the green body after cold isostatic pressing can reach 56%. This step helps to increase the uniformity of shrinkage in subsequent sintering.

[0117] Sintering: Place the green body after cold isostatic pressing in a tubular sintering furnace and evacuate to a vacuum degree of 6×10^-4Pa. Heating rate is increased to 600℃ at 3℃ / min, and heat preservation is carried out for 6 hours to remove residual impurities, and then high-purity argon is introduced. Then, heating is carried out to 900℃ at a heating rate of 2℃ / min and heat preservation is carried out for 4 hours to promote sintering and structural densification. Finally, the green body is cooled to room temperature by programmed cooling to obtain a co-sintered multilayer ceramic structure; the porosity of the multilayer ceramic structure is 6%.

[0118] Current collector coating: A 10 μm thick metal Al film was coated on the side of the prepared ceramic sheet that was not sprayed with LLZO electrolyte powder by magnetron sputtering under Ar gas protection to serve as the current collector of the composite electrode.

[0119] Preparation of negative electrode

[0120] A polymer solid electrolyte layer is sprayed on the surface of the metal lithium foil. The thickness of the polymer solid electrolyte layer is 20 μm. The polymer solid electrolyte is PEO, and the lithium salt is LiPF6 with a concentration of 15 wt%.

[0121] Series high voltage battery assembly:

[0122] The positive electrode and negative electrode prepared above are compounded with a composite current collector to obtain a battery unit. The composite current collector includes a protective layer and a negative electrode current collector on one side of the protective layer. The protective layer is coated with a conductive glue on the side close to the positive electrode. Four battery units are stacked in sequence and warm isostatically pressed at 120°C and 100MPa for 30 minutes to ensure close contact between the layers. The number of stacking layers is 4.

[0123] Example 2

[0124] Preparation of multilayer ceramic structures:

[0125] Raw material preparation and mixing: NCM532 powder with an average particle size of 8 μm and LLTO powder with a particle size of 400 nm were added into a ball mill at a mass ratio of 97:3; an appropriate amount of isopropyl ketone was added as a grinding aid, and the powder was ball milled at a speed of 500 rpm for 24 hours to ensure that the powder was evenly dispersed; after ball milling, the powder was placed in an oven at 80°C for 6 hours for drying.

[0126] Powder molding: The dried powder is ground and sieved to remove lumps; the uniform powder is loaded into a mold and hydraulically molded at a pressure of 20 MPa to obtain a green body of the positive electrode active material layer.

[0127] Electrolyte spraying and cold isostatic pressing: A 10μm thick layer of LLZO electrolyte powder is sprayed on the surface of the green body of the positive electrode active material layer, wherein the particle size of the LLZO electrolyte powder is 400nm; the green body after spraying is placed in a cold isostatic pressing device and cold isostatically pressed at a pressure of 180MPa to increase the density of the green body. The processing time is about 10 minutes, and the relative density of the green body after cold isostatic pressing can reach 53%.

[0128] Sintering: Place the green body after cold isostatic pressing in a tubular sintering furnace and evacuate to a vacuum degree of 6×10^-4Pa. Heating is increased to 600℃ at a heating rate of 3℃ / min and kept for 6 hours to remove residual impurities, followed by the introduction of high-purity argon. Then, heating is performed to 850℃ at a heating rate of 2℃ / min and kept for 4 hours to promote sintering and structural densification. Finally, the green body is cooled to room temperature by programmed cooling to obtain a co-sintered multilayer ceramic structure; the porosity of the multilayer ceramic structure is 8%.

[0129] Preparation of negative electrode

[0130] A polymer solid electrolyte layer is sprayed on the surface of the metal lithium foil, the thickness of the polymer solid electrolyte layer is 20 μm, wherein the polymer solid electrolyte is PEO, and the lithium salt is Li PF6, and the concentration is 15wt%;

[0131] Series high voltage battery assembly:

[0132] The positive electrode, negative electrode and composite current collector are stacked in the same order to form a battery unit. The middle of the composite current collector is a PET layer, and the PET layer is provided with aluminum foil on the side close to the positive electrode, and the PET layer is provided with copper foil on the side close to the negative electrode. The stacked battery unit is subjected to warm isostatic pressing at 120°C and 100MPa for 30 minutes to ensure close contact between the layers. The number of stacking layers is 4.

[0133] Cycle performance test:

[0134] 1. At 45°C, charge to 4.2V at 0.1C constant current and constant voltage, cut-off current 0.05C, and let stand for 20 minutes;

[0135] 2. At 45°C, discharge at 0.1C constant current to 2.75V and let stand for 20 minutes;

[0136] 3. Repeat steps 1 and 2 until the capacity retention rate reaches 80%, and record the number of cycles.

[0137] After testing, Example 1 cycled for 216 cycs, and Example 2 cycled for 145 cycs. This shows that the present application realizes an internally series-connected multilayer ceramic solid-state lithium-ion battery through multilayer ceramic co-firing technology in conjunction with a composite current collector, and matches a metallic lithium negative electrode, thereby improving the battery energy density and broadening the application scope of the multilayer ceramic technology. At the same time, the preparation method of the present application composites multilayer ceramics, a current collector, and a metallic lithium negative electrode through an isostatic pressing process to obtain a stable internally series-connected high-voltage battery cell.

[0138] And by comparing Example 1 and Example 2, it can be seen that the method of the present application, which involves spraying a current collector on the surface of the positive electrode and then compositely forming the multilayer ceramic and the composite current collector by isostatic pressing, has better cycle performance than Example 2.

Claims

1. A solid-state lithium-ion secondary battery, characterized in that: A battery cell having at least two or more than two battery cells including a positive electrode, a negative electrode and a solid electrolyte layer; The positive electrode and the solid electrolyte layer form the multilayer ceramic structure, and the multilayer ceramic structure is an integrated structure; A polymer layer is provided between the solid electrolyte layer and the negative electrode; The negative electrode comprises metallic lithium; Two adjacent battery cells are electrically connected in series.

2. The solid-state lithium-ion secondary battery according to claim 1, characterized in that: The porosity of the multilayer ceramic structure is less than 10%; Preferably, the porosity of the multilayer ceramic structure is <5%.

3. The solid-state lithium-ion secondary battery according to claim 1, characterized in that: The positive electrode includes a positive electrode active material layer and a positive electrode current collector, wherein the positive electrode current collector is arranged on a side of the positive electrode active material layer away from the solid electrolyte layer. In the solid lithium ion secondary battery, at least one positive electrode current collector is electrically connected to the adjacent negative electrode.

4. The solid-state lithium-ion secondary battery according to any one of claims 1 or 2, characterized in that: The negative electrode includes a negative electrode current collector, and the negative electrode current collector is arranged between the positive electrode active material layer of the adjacent battery unit and the negative electrode or is arranged at the outermost side of the solid-state lithium ion secondary battery.

5. The solid-state lithium-ion secondary battery according to claim 1, characterized in that: A composite current collector layer is also arranged between the positive electrode and the negative electrode. The composite current collector includes a protective layer and a metal layer arranged on both sides of the polymer layer, and the two metal layers are electrically connected.

6. The solid-state lithium-ion secondary battery according to claim 1, characterized in that: The polymer layer includes a polymer solid electrolyte and a lithium salt.

7. The solid-state lithium-ion secondary battery according to claim 1, characterized in that: The solid electrolyte layer includes an oxide solid electrolyte.

8. The solid-state lithium-ion secondary battery according to claim 1, characterized in that: The metal lithium negative electrode includes one or more of lithium foil, lithium sheet, and lithium-indium alloy.

9. The method for preparing a solid-state lithium-ion secondary battery according to claim 1, characterized in that: The steps include: S1. Preparing a multilayer ceramic structure comprising a positive electrode active material layer and a solid electrolyte layer; S2. The multilayer ceramic structure, polymer layer and lithium metal negative electrode prepared in the composite step SI are formed into a battery cell; and / or, the prefabricated sheet composed of the polymer layer and the lithium metal negative electrode and the multilayer ceramic structure prepared in the step S1 are formed into a battery cell; S3. Stacking two or more battery cells prepared in step S2 and isostatically pressing to prepare a battery cell, wherein the positive electrodes and negative electrodes of two adjacent battery cells are connected.

10. The preparation method according to claim 9, characterized in that: In the step S1, the positive electrode active material layer and the solid electrolyte layer are compounded to form a composite structure; and the composite structure is co-sintered under an inert atmosphere to obtain a multilayer ceramic structure.

Citation Information

Patent Citations

  • Composite positive electrode material, lamination unit, preparation method and all-solid-state lithium ion battery

    CN109560248A

  • Polymer in-situ modified inorganic solid electrolyte ceramic wafer and preparation

    CN111934001A

  • Asymmetric solid electrolyte and preparation method thereof as well as solid lithium battery and preparation method thereof

    CN114614079A

  • High-energy-density lithium-rich all-solid-state lithium battery and preparation method thereof

    CN115172883A

  • Lithium lanthanum zirconium oxide all-solid-state battery and preparation method thereof

    CN117558992A